The Effect of Providing Education Through Audio Visual on Knowledge of Handling Dysminorrhea in Adolescent Girls at Kader Bangsa Health Vocational School in Palembang - Ranida Arsi; Fitri Afdhal; Inda Helmika (MultiTech Publisher, 2023)
Dysmenorrhea is a menstrual disorder that is often experienced by young women. Dysmenorrhea is felt as pain in the lower abdomen and can also be felt in the pelvis, lower back or thighs. Dysmenorrhea arises due to disorders of the reproductive organs, hormonal factors and psychological factors which can disrupt daily activities (Lasmawanti et al., 2021). This study aims to determine the effect of providing education via audio-visual on knowledge of treating dysmenorrhea in adolescent girls. This research used a Quasy experiment one group pre and post test design with a sample size of 26 female students. The statistical test used is the Wilcoxon sign rank test. The research results show that there is a significant effect with a p value of 0.000 (<0,05).